A Meeting of Angels: The Correspondence of Thomas Merton with Edward Deming & Faith Andrews - Doriot, Sister Jeanne (Cistercian studies quarterly, 2011)
The article reviews the book "A Meeting of Angels: The Correspondence of Thomas Merton With Edward Deming & Faith Andrews," edited by Paul Pearson.